2017
DOI: 10.1039/c7tc01339f
|View full text |Cite
|
Sign up to set email alerts
|

Molding hemispherical microlens arrays on flexible substrates for highly efficient inverted quantum dot light emitting diodes

Abstract: Microlens arrays were introduced into a QLED and the EQE of the device was enhanced by a factor of 64%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The higher improvement value might result from the distribution discrepancy between the actual AgNWs network stack and the Monte–Carlo simulation–generated penetrated‐network model; better results can be further achieved if AgNWs network structure is carefully studied and designed. Figure presents the CE evolution of red FQLEDs with both vacuum and solution‐processed TCEs during the past one decade, which clearly demonstrates that our FQLED with solution‐processed AgNWs TCEs outperforms the state‐of‐the‐art FQLEDs and reaches a new efficiency level, encouraging the development of flexible light‐emitting devices.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The higher improvement value might result from the distribution discrepancy between the actual AgNWs network stack and the Monte–Carlo simulation–generated penetrated‐network model; better results can be further achieved if AgNWs network structure is carefully studied and designed. Figure presents the CE evolution of red FQLEDs with both vacuum and solution‐processed TCEs during the past one decade, which clearly demonstrates that our FQLED with solution‐processed AgNWs TCEs outperforms the state‐of‐the‐art FQLEDs and reaches a new efficiency level, encouraging the development of flexible light‐emitting devices.…”
Section: Resultsmentioning
confidence: 83%
“…Here, by utilizing AgNWs as flexible TCEs and the light extraction structure, we successfully demonstrate a highly efficient red FQLED based on a standard inverted structure with the maximum EQE and CE reaching 24.1% and 19.5 cd A −1 , respectively. The efficiency is improved 4.4 and 3 times for EQE and CE, respectively, compared with that of the reference QLED with glass/ITO TCEs and 1.7 times compared with that of the most efficient previous FQLED . Also, it is competitive to the reported exceedingly efficient rigid QLEDs with a similar device structure .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…8,9 Numerous studies have reported that the light extractions of OLEDs and QLEDs could be enhanced through introduction of internal or external light-extraction layers. [10][11][12][13][14] For example, we have demonstrated that introducing internal PEDOT:PSS grating nanostructures can effectively extract the waveguided light from QLEDs by nanoimprint lithography techniques. 15 However, the extraction of the trapped light to WG and SPP modes is more challenging since the insertion of internal structures inside the QLEDs always changes the morphology of the quantum dot emitting layers and then deteriorates the performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Microlens and microlens array (MLA) with diameters of a few to hundreds micrometers have wide applications in various fields, including artificial compound eyes [1], light-emitting devices [2], microfluidic system [3], sensors [4], and so on. These applications require the fabrication of microlens arrays on different substrates or even on curved surfaces, thus requiring achievable microlens fabrication processes.…”
Section: Introductionmentioning
confidence: 99%